Prediction of peroxide value in omega-3 rich microalgae oil by ATR-FTIR spectroscopy combined with chemometrics - Cebi, Nur; Yilmaz, Mustafa Tahsin; Sagdic, Osman; Yuce, Hande; Yelboga, Emrah (ELSEVIER SCI LTD, 2017)
Our work explored, for the first time, monitoring peroxide value (PV) of omega-3 rich algae oil using ATR-FTIR spectroscopic technique. The PV of the developed method was compared by that obtained by standard method of Association of Official Analytical Chemists (AOAC). In this study, peak area integration (PAI), Partial Least Squares Regression (PLSR), and Principal Component Regression (PCR) were used as the calibration techniques. PV obtained by the AOAC method and by FTIR-ATR technique were well correlated considering the peak area related to trans double bonds and chemometrics techniques of PLSR and PCR. Calibration model was established using the band with a peak point at 966 cm(-1) (990-940 cm(-1)) related to C-H out of plane deformation vibration of trans double bond. Algae oil oxidation could be successfully quantified using PAL PLSR and PCR techniques. Additionally, hierarchical cluster analysis was performed and significant discrimination was observed coherently with oxidation process. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Peroxide value; Oxidation; Algae oil; ATR-FTIR; Chemometrics; TRANSFORM INFRARED-SPECTRA; OXIDATIVE STABILITY; EDIBLE OILS; REGRESSION; FATS; Chemistry; Food Science & Technology; Nutrition & Dietetics